PENGARUH SUSTAINABILITY REPORT, PROFITABILITAS DAN FIRM SIZE, TERHADAP NILAI PERUSAHAAN DENGAN MEDIA EKSPOSURE SEBAGAI VARIABEL MODERATING - Yunan, Nadiya (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study is to examine and analyze the effect of profitability and firm size on firm value. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2016 – 2021. The total sample in this study is 61 companies. The result of this research is that profitability has a negative effect and firm size has a positive effect on firm value.